An Error Analysis On Learning Passive Voice Of The Second Year Students Of Smp N 1 Polanharjo Klaten In Academic Year 2011/2012 - JATMIKO., SIGIT TRI (2012)
This study aims at knowing the kinds of passive voice errors as a result of analyzing the errors and to find the most common type of error. The result of the study is intended to give contribution to the teaching and learning English. The research was done to the second year students of SMP N 1 POLANHARJO KLATEN. As the sample, the writer took 40 students of VIIIA class. The data were collected through observation and documentation. The type of the study is descriptive qualitative method. To analyze the data, the writer uses the surface strategy taxonomy. It means that the writer classifies the errors based on the type of errors. The result of the research paper shows that the kinds of passive voice errors done by the students are addition, omission, miss ordering, and misinformation. After analyzing the data, the writer can conclude that the numbers of errors are 18 sentences, which consist of error in omission 5 sentences, addition 4 sentences, miss ordering 4 sentences, and misinformation 5 sentences. Based on the analyses and the classification of error into their types, the writer can conclude that the most common type of error made by the students is misinformation error.